Ho Chi Minh Ville, des inondations à la submersion… - Georges Vachaud; Nicolas Gratiot; Tien Dung Tran Ngoc (EchoGéo)
Most of the mega-cities in South-East Asia located on the coast are subject to both very strong demographic growth and increased flood risks resulting from a combination of poorly controlled urban development, increased monsoon rainfall intensity, rising sea levels and subsidence. Ho Chi Minh City is a typical example of this situation, which could lead in the medium to short term to the submergence of the majority of recent districts built on former marshland or rice fields. It is therefore essential to implement appropriate risk management strategies and to develop the region in a sustainable manner.